Letter (copy) : Donations
041-0159-001 LK/FP/447 Finance. 9th September, 1936. Dr. C. Brook, Spanish Medical Aid Committee, 24-28, New Oxford Street, London, W.C.1. Dear Dr. Brook, Donations. Will you kindly acknowledge as hereunder the receipt of the enclosed remittances. Mr. G. Reilly, 3, George Street West, Luton 5s. 0d. Mr. P.A. Jordon, Gillingham branch of Transport & General Workers' Union, 31, Albert Road, Chatham. 10s. 0d. Mr. Harris, Edmonton Labour Party, 372, Fore Street, Edmonton 17 pesetas. 13 French francs. Thanking you, Yours sincerely, Finance Department. ENCS. 292/946/41/159